Analisis Faktor Yang Mempengaruhi Keputusan Mahasiswa Berinvestasi Reksa Dana Syariah Pada Aplikasi Bibit Di Sumatera Utara - Yolanda, Tata Felina; Ikhsan Harahap, Muhammad; Ramadani Silalahi, Purnama (Universitas Hamzanwadi, 2024)
This research was conducted to determine the analysis of factors that influence students decisions to invest in sharia mutual funds in the Bibit application in North Sumatra. The population in this study consisted of enrolled students in North Sumatra, and the sampling strategy employed was purposive sampling, yielding a total of 100 respondents. The study was conducted using the SPSS 15 software test tool and multiple linear regression analysis tests. In order to gather data for this study, online questionnaires with a Likert scale were sent, and multiple linear regression analysis was carried out using the SPSS version 15 software. The study's findings suggest that while wealth has little bearing on investment decisions, financial literacy does, and that investment decisions are influenced by ease of application